Ruptured endometrioma mimicking ovarian malignancy: a case report and literature review - Seelam, Radha Rani; Varun, Neha; Meena, Jyoti; Kumari, Rajesh; Dadhwal, Vatsla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
In current practice endometriosis is a rising concern, involving all age groups and relatively less prevalent in perimenopausal age groups. It has a variety of presenting symptoms in perimenopausal age group including severe dysmenorrhoea, dyspareunia, infertility, chronic pelvic pain, abdominopelvic mass, acute abdomen with peritonitis and non-specific symptoms like gastritis, diarrhoea, rectal bleeding. High index of suspicion should be there to diagnose a ruptured endometrioma in a perimenopausal female with adnexal mass, peritonitis features and rising serum CA-125 and CA19.9 levels. Here we present a case of ruptured endometrioma mimicking ovarian malignancy in a perimenopausal female.